Angina relates to coronary flow in women with ischemia and no obstructive coronary artery disease. (15th June 2021) - Suppogu, Nissi; Wei, Janet; Quesada, Odayme; Shufelt, Chrisandra; Cook-Wiens, Galen; Samuels, Bruce; Petersen, John W.; Anderson, R. David; Handberg, Eileen M.; Pepine, Carl J.; Bairey Merz, C. Noel
Abstract: Background: Women with suspected ischemia and no obstructive coronary artery disease (INOCA) often have coronary microvascular dysfunction (CMD) as measured by impaired coronary flow reserve (CFR), which is associated with angina and adverse cardiovascular events. CFR is a ratio of hyperemic to baseline average peak velocity (bAPV), and the relation of baseline flow to angina is not understood. Methods: We evaluated 259 women enrolled in the WISE-Coronary Vascular Dysfunction (WISE-CVD) project with suspected CMD who underwent invasive coronary functional testing. We analyzed variables stratified by high (e.g. ≥22 cm/s) vs low (<22 cm/s) bAPV, using t- test or Wilcoxon rank; linear and multivariable regression was used with bAPV as a continuous variable. Results: Women with high bAPV had worse Seattle Angina Questionnaire (SAQ) angina frequency (58 ± 26 vs 67 ± 25, p = 0.005) and SAQ-7 scores (57 ± 22 vs 62 ± 21, p = 0.03), with higher nitrate ( p = 0.02) and ranolazine use (p = 0.03). The high bAPV subgroup also had lower CFR ( p < 0.001)). Linear regression related higher bAPV with lower SAQ-7 ( p = 0.01) and lower angina frequency scores ( p = 0.001). These results remained significant in multivariable modelling adjusting for baseline differences ( p < 0.04). SAQ-7 was significantly predicted by bAPV. Conclusions: Among women with suspected INOCA, angina relates to high bAPV, a result supported by the concomitant greater use of anti-anginal drugs. These results suggest that high bAPV contributes to impaired CFR and may represent a specific pathophysiologic contributor to CMD and may be a treatment target in INOCA subjects. Highlights: Our cohort includes women with ischemia with non-obstructive coronary arteries. Coronary microvascular dysfunction is often diagnosed by impaired CFR. Relationship with angina and components of CFR has not been studied previously. Women with higher baseline coronary flow velocity had more angina and lower CFR. Higher baseline coronary flow velocity may be a therapeutic target for angina.